Orientalism - Said, Edward W (New York : Vintage Books, 2003)
The author presents a critique of the Western World's historical, cultural, and political perceptions of the East and Arab people. In this study, the author traces the origins of the West's concept of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East
-- The scope of orientalism. I. Knowing the Oriental ; II. Imaginative geography and its representations : orientalizing the Oriental ; III. Projects ; IV. Crisis -- Orientalist structures and restructures. I. Redrawn frontiers, redefined issues, secularized religion ; II. Silvestre de Sacy and Ernest Renan : Rational anthropology and philogical laboratory ; III. Oriental residence and scholarship : the requirements of lexicography and imagination ; IV. Pilgrims and pilgrimages, British and French -- Orientalism now. I. Latent and manifest orientalism ; II. Style, expertise, vision: orientalism's worldliness ; III. Modern Anglo-French orientalism in fullest flower ; IV. The latest phase -- Afterword -- Notes -- Index
Includes bibliographical references and index
Keywords: Orientalism; Asia -- Foreign public opinion; Middle East -- Foreign public opinion; Asia -- Study and teaching; Middle East -- Study and teaching; Imperialism; East and West